Antecedents of Consumer Purchase Intention of Fashion Products - Eddy Madiono Sutanto; Yana Widianto (Master of Management, School of Business and Management, Petra Christian University, 2023)
Fashion products are such dynamic products. Therefore, understanding well to consumer intention is very important for producers as well as distributors. This study aimed to determine the effect of credibility, attractiveness, product suitability with personality, and celebrity recognition on consumer purchase intentions of Greenlight fashion products. The research data was collected using a questionnaire distributed to 109 respondents aged 15–31 years who knew Ariel Noah as a Greenlight product ad star, had seen Greenlight product advertisements, and had bought Greenlight fashion products. The data was processed using the multiple linear regression method. The results suggested that the credibility, attractiveness, and suitability of products with celebrity personalities positively and significantly affected consumers' purchase intentions of Greenlight fashion products. However, celebrity recognition had no significant effect on consumer purchase intentions for Greenlight fashion products. By considering the results, the stakeholders shall adjust their strategies to keep and enlarge their market shares further.